The effects of project-based learning on secondary school students' speaking skills - Huỳnh Vũ Nguyên (Trường Đại học Trà Vinh, 2020)
To examine the effectiveness of project-based learning in raising students’ speaking performances. To explore learners’ evaluations of project based learning implementation and their attitudes towards project-based learning in speaking lessons.